Managing risk and resilience in the supply chain - Kaye, David (BSI Business Information, 2008)
This book is an invaluable resource for any business or organization that depends on outsourced supply and delivery chains. It takes a practical approach to managing risk and resilience, to guide you through the minefield associated with the supply chain, in order to shape a suitable management strategy. It takes a close look at how the various parties involved manage the agendas necessary to implement a risk strategy. This publication looks at the ways that supply chains can fail, either suddenly or gradually, over a period of time. It discusses the opportunities, and analyzes the threats, in order to gain an understanding of the strategic risk and management of supply chains. ... Modern supply chain management is more than subcontracting. It can mean passing over a crucial part of the organization to a third party. It doesn't only pass to outsiders the responsibility to deliver on time and in the expected quality. Increasingly organizations are replacing their own people, technology, intellectual assets and other crucial elements of their business to outsiders. -- Publisher description.
Keywords: Business logistics.; Risk management.; elektronické knihy; electronic books